The theoretical approach to artificial intelligence and its importance in enhancing administrative functions in sports institutions - Melki, oussama; Saidane, saad (sports creativity, 2024)
All sports institutions compete to achieve their success by exploiting their financial and human resources to achieve their goals, but the current era depends on artificial intelligence to achieve more efficient and faster performance. This study aimed to learn about artificial intelligence and some of the terminology related to it and to highlight the various uses of artificial intelligence. We also touched on the misuse and positives of the use of artificial intelligence, and finall we touched on its importance in enhancing the function of planning, organizing and directing in sports institutions.